1995
DOI: 10.1111/j.1447-0756.1995.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Expression of Sialyl Tn Antigen in Gynecologic Tumors

Abstract: These findings indicate different behaviors in the appearance of STN in tumor tissue and blood circulation, and also suggest the possible applicability of STN to immunohistochemical diagnosis of squamous-cell carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…in many cancers (25,26), including cervical (27,28), lung adenocarcinomas (29), colorectal carcinomas (30), breast carcinomas (31), and gastric carcinomas (32). Many studies over the past 30 years have shown that the Tn antigen is expressed by >80% of human carcinomas (5-7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in many cancers (25,26), including cervical (27,28), lung adenocarcinomas (29), colorectal carcinomas (30), breast carcinomas (31), and gastric carcinomas (32). Many studies over the past 30 years have shown that the Tn antigen is expressed by >80% of human carcinomas (5-7).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to examine cervical cancer because it has been well documented that Tn and STn antigens are expressed in at least 60% of human cervical carcinomas and their expression is associated with the poor prognosis of the disease (27,28). However, until now, there has been no genetic or biochemical basis for the expression of the Tn/STn antigens in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, normal ovarian epithelia were always found to be STn negative [35,36,37] Some testis cells were occasionally found to be STn positive such as Leydig cells or interstitial cells [1,14,22]. Finally, STn was found at the apical membrane of the ciliated cells of the lung [17,22,38] and at the apical side of the ductal epithelium in normal breast tissue [39,40,41].…”
Section: Stn Immunodetection In Tissues and Tumorsmentioning
confidence: 99%
“…In these different cases, STn over-expression was primarily observed at the apical or luminal cell surface as well as in the corresponding healthy tissues. More unexpectedly, STn was also reported in benign lesions in pancreas [46] and ovaries [35,36,37], two tissues that are devoid of STn expression in the healthy state. Notably, STn staining was observed in pancreatic intraepithelial neoplasia stage III (PanIN3), the last histological grade relevant to benign tumor before the tumor becomes invasive, but not in earlier stages [46,47].…”
Section: Stn Immunodetection In Tissues and Tumorsmentioning
confidence: 99%
“…[272][273][274] Im Unterschied dazu wurde in normalen, erwachsenen Geweben keine oder nur wenig Expression beobachtet. In vielen Krebsarten, einschließlich Zervixkrebs, [275,276] Adenokarzinom der Lunge, [277] kolorektales Karzinom, [278] Brustkarzinom [279] und Magenkarzinom, [280] korreliert die Expression des Tn-Antigens mit dem metastatischen Potenzial und einer schlechten Prognose.…”
Section: Krebsunclassified